2017
DOI: 10.1111/mpp.12569
|View full text |Cite
|
Sign up to set email alerts
|

Verticillium dahliae transcription factor VdFTF1 regulates the expression of multiple secreted virulence factors and is required for full virulence in cotton

Abstract: Fungal transcription factors (TFs) implicated in the regulation of virulence gene expression have been identified in a number of plant pathogens. In Verticillium dahliae, despite its agricultural importance, few regulators of transcription have been characterized. In this study, a T-DNA insertion mutant with significantly reduced virulence towards cotton was identified. The T-DNA was traced to VdFTF1, a gene encoding a TF containing a Fungal_trans domain. Transient expression in onion epidermal cells indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 87 publications
1
37
0
Order By: Relevance
“…Thus far, dozens of genes regulating virulence in V . dahliae (Fradin and Thomma, ; Klimes et al ., ; Zhang et al ., ) on various hosts have been identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, dozens of genes regulating virulence in V . dahliae (Fradin and Thomma, ; Klimes et al ., ; Zhang et al ., ) on various hosts have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…This fungus infects host plants by directly penetrating roots and subsequently and systematically colonizing the water-conducting xylem vessels, until the pathogen switches to the reproductive mode when it produces conidia and toxins that interfere with the water movement that eventually results in leaf wilting and plant death (Klosterman et al, 2009;Zhang et al, 2019). Thus far, dozens of genes regulating virulence in V. dahliae (Fradin and Thomma, 2006;Klimes et al, 2015;Zhang et al, 2017b) on various hosts have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the head blight‐causing fungus Fusarium graminearum 26% of 657 tested transcription factors showed a phenotypic effect during mycelial growth, conidia production and toxin production (Son et al , ). In summary, a number of transcription factors, which play important roles in host infection and pathogenesis, have been identified for several important crop pathogens (Chen et al , ; Okmen et al , ; Xiong et al , ; Zhang et al , ; Zhuang et al , ). In Z. tritici , however, only a few regulatory genes have been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Verticillium dahliae is a notorious fungal pathogen that attacks a wide range of hosts, targets the xylem tissue, and causes verticillium wilt disease on many economically important crops (Klosterman et al , ; Inderbitzin and Subbarao, ). Previous studies have shown that secreted proteins probably play a critical role in the pathogenesis of V. dahliae (Fradin and Thomma, ; Chu et al , ; Chen et al , ; ; Zhang et al , ), and the function or the activity of several secreted proteins have been elucidated (de Sain and Rep, ; Klimes et al , ; Wang et al , ; Zhang et al , ). Similar to the mechanisms discovered in other phytopathogens, V. dahliae secretes proteins to manipulate host immunity during infection (de Jonge et al , ; Zhou et al , ; Santhanam et al , ; Liu et al , ; Gui et al , , ; Kombrink et al , ; Zhang et al , ; Qin et al , ).…”
Section: Introductionmentioning
confidence: 99%